Impact of Triplet Excited States on the Open‐Circuit Voltage of Organic Solar Cells. Issue 21 (20th April 2018) - Benduhn, Johannes; Piersimoni, Fortunato; Londi, Giacomo; Kirch, Anton; Widmer, Johannes; Koerner, Christian; Beljonne, David; Neher, Dieter; Spoltore, Donato; Vandewal, Koen
Abstract: The best organic solar cells (OSCs) achieve comparable peak external quantum efficiencies and fill factors as conventional photovoltaic devices. However, their voltage losses are much higher, in particular those due to nonradiative recombination. To investigate the possible role of triplet states on the donor or acceptor materials in this process, model systems comprising Zn‐ and Cu‐phthalocyanine (Pc), as well as fluorinated versions of these donors, combined with C60 as acceptor are studied. Fluorination allows tuning the energy level alignment between the lowest energy triplet state (T1 ) and the charge‐transfer (CT) state, while the replacement of Zn by Cu as the central metal in the Pcs leads to a largely enhanced spin–orbit coupling. Only in the latter case, a substantial influence of the triplet state on the nonradiative voltage losses is observed. In contrast, it is found that for a large series of typical OSC materials, the relative energy level alignment between T1 and the CT state does not substantially affect nonradiative voltage losses. Abstract : High nonradiative voltage losses in organic solar cells do not originate from local excited triplet states of the electron donating or accepting material . A systematic study of metal–phthalocyanine:C60 blends and a broad literature‐based comparison show that the relative energy alignment of triplet excited and charge‐transfer state affects the nonradiative losses only in very specific cases of Cu containing compounds.